Interventions to support risk and benefit understanding of disease-modifying drugs in Multiple Sclerosis patients: A systematic review - Reen, G; Silber, E; Langdon, D (Elsevier, 2018)
Objective: The present review evaluates interventions that have been designed to improve understanding of the complex risk-benefit profiles of disease-modifying drugs (DMDs) in patients with Multiple Sclerosis (MS). Methods: A systematic search conducted using PubMed, Embase, Google Scholar and PsycINFO identified 15 studies. Interventions which provided treatment information were present across a range of study designs. A narrative synthesis was conducted due to heterogeneity of research findings. Results: Interventions providing treatment information ranged from comprehensive education programmes to booklets of a few pages. MS patients favoured the interventions they received. Understanding of overall treatment information and treatment risks specifically, generally improved following interventions. Yet overestimation of treatment benefits persisted. There was no conclusive effect on DMD decisions. No superior intervention was identified. Conclusion: Interventions designed to improve understanding of DMD risk and benefit information are moderately successful. Practice implications: Additional support provided to MS patients beyond routine healthcare can generally improve understanding of the complex risk-benefit profiles of DMDs. Future interventions need to ensure that patients with symptoms that may confound understanding can also benefit from this additional information.